Convergent transcription induces transcriptional gene silencing in fission yeast and mammalian cells. - Gullerova, M; Proudfoot, N (2012)
We show that convergent transcription induces transcriptional gene silencing (TGS) in trans for both fission yeast and mammalian cells. This method has advantages over existing strategies to induce gene silencing. Previous studies in fission yeast have characterized TGS as a cis-specific process involving RNA interference that maintains heterochromatic regions such as centromeres. In contrast, in mammalian cells, gene silencing is known to occur through a post-transcriptional mechanism that uses exogenous short interfering RNAs or endogenous microRNAs to inactivate mRNA. We now show that the introduction of convergent transcription plasmids into either Schizosaccharomyces pombe or mammalian cells allows the production of double-stranded RNA from inserted gene fragments, resulting in TGS of endogenous genes. We predict that using convergent transcription to induce gene silencing will be a generally useful strategy and allow for a fuller molecular understanding of the biology of TGS.